Development of a CRISPR/Cas9-integrated lateral flow strip for rapid and accurate detection of Salmonella. (December 2022) - Wang, Haoyu; Wu, Qian; Zhou, Mengyang; Li, Chao; Yan, Chao; Huang, Lin; Qin, Panzhu
Abstract: Rapid and accurate detection of foodborne pathogens is crucial for safeguarding human health. Herein, we constructed a clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9-integrated lateral flow strip (Cas9-LFS) for detecting Salmonella . A primer set targeting the fimA gene of Salmonella spp. was used to amplify all Salmonella serovars. After extraction, the genomic DNA of Salmonella was amplified with unlabelled forward primer and FITC-labelled reverse primer, thus producing numerous FITC-labelled amplicons that can be precisely recognized by Cas9 complexed with a specific single-guide RNA (sgRNA). When loaded on the LFS, the complexes of amplicons and Cas9/sgRNA can act as bonds to anchor gold nanoparticles to the test line, resulting in a visible color change. This design makes Cas9-LFS more powerful than conventional LFS in eliminating false-positives caused by primer dimers. By using Salmonella Typhimurium as a reference strain, Cas9-LFS achieved a limit of detection as low as 10 2 CFU/mL and showed good accuracy in distinguishing Salmonella -contaminated milk. We expect this unique strategy to open a new window for building versatile pathogen detection tools. Highlights: A CRISPR/Cas9-integrated LFS (Cas9-LFS) was constructed for accurate and visual detection of Salmonella. Primer-dimer interference that is inevitable in conventional amplifications can be totally overcome with the method. As low as 10 2 CFU/mL of Salmonella can be well measured with the constructed method. Salmonella -contaminated milk samples have been measured with considerable accuracy.